Dr. First - Hargreaves, Adam (Penguin Books, 2017)
The greatest mash-up in the entire Whoniverse is here! Doctor Who meets Roger Hargreaves' Mr Men in this new series of stories, written and illustrated by Adam Hargreaves. In Dr. Eleventh, join the Eleventh Doctor and River Song on an amazing new adventure through time and space